2020
DOI: 10.1186/s13063-020-04669-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Jia Wei Bushen Yiqi formulas as an adjunct therapy to systemic glucocorticoids on acute exacerbation of COPD: study protocol for a randomized, double-blinded, multi-center, placebo-controlled clinical trial

Abstract: Background Systemic glucocorticoids are effective for the management of chronic obstructive pulmonary disease (COPD) exacerbation but have serious adverse effects. Traditional Chinese medicine (TCM) can bring additional benefits to these patients but has few adverse effects. The present study aims to evaluate the efficacy and safety of Jia Wei Bushen Yiqi (JWBY) formulas in patients who suffer from COPD exacerbations and to investigate whether the short-term (5-days) systemic glucocorticoid therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The patients will be randomly divided into the MBYF group or the placebo group in a 1:1 ratio. Blinding will be performed as previously described [ 31 ]. Briefly, random numbers will be placed in a closed and opaque envelope without access to directly involved individuals in the study.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The patients will be randomly divided into the MBYF group or the placebo group in a 1:1 ratio. Blinding will be performed as previously described [ 31 ]. Briefly, random numbers will be placed in a closed and opaque envelope without access to directly involved individuals in the study.…”
Section: Methods and Analysismentioning
confidence: 99%
“…MBYF consists of five herbs, as shown in Table 1 [ 29 31 ]. Furthermore, in vivo and in vitro experiments show that MBYF and its compounds can significantly adjust inflammation and immunology [ 29 , 30 , 32 – 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rat dose of 12.5 g/kg was calculated as 9.1× human dose. The human dose of 125 g/70 kg is referenced to the clinical dose from our two clinical trials (14,19). Five herbal formulas were dissolved in ultrapure water every three days and stored at 4°C.…”
Section: Mbyf Preparationmentioning
confidence: 99%
“…17 However, MBYF was confirmed to relieve symptoms, reduce deterioration and improve lung function for COPD patients in clinical treatment. 18,19 Network pharmacology is a new discipline based on a systems biology approach that manages large amounts of data through computation and system analysis to predict drug targets and signaling pathways. 20,21 It mainly investigates the mechanism of drug action and related pathways 21,22 and the complex interactions between biological systems, diseases, and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A study indicated that the treatment of COPD by traditional Chinese medicine (TCM) has increased significantly 17 . However, MBYF was confirmed to relieve symptoms, reduce deterioration and improve lung function for COPD patients in clinical treatment 18,19 …”
Section: Introductionmentioning
confidence: 99%